2017
DOI: 10.1111/acem.13124
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frailty on 30‐day Mortality Risk in Older Patients With Acute Heart Failure Attended in the Emergency Department

Abstract: The presence of frailty is an independent risk factor of 30-day mortality in nonsevere dependent older patients attended with AHF in EDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 39 publications
(66 reference statements)
1
19
0
1
Order By: Relevance
“…Table 1 summarizes the characteristics of the ten studies included in the systematic review. Four studies were conducted in Italy [ 20 , 22 , 26 , 28 ], three in the USA [ 19 , 25 , 27 ], and three in Spain [ 21 , 23 , 24 ]. In total, the studies included 3033 elderly patients with HF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the characteristics of the ten studies included in the systematic review. Four studies were conducted in Italy [ 20 , 22 , 26 , 28 ], three in the USA [ 19 , 25 , 27 ], and three in Spain [ 21 , 23 , 24 ]. In total, the studies included 3033 elderly patients with HF.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were classified as “Physical Frailty” as they primarily used physical frailty assessment tools such as the Fried Frailty Phenotype (FP) measurement [ 19 , 21 , 23 , 24 , 27 ], portions of the five FP indicators (e.g., gait speed or handgrip strength)[ 25 , 28 ], or the Short Physical Performance Battery (SPPB) [ 26 ]. Two studies were classified as “Multidimensional Frailty” as they used a multidimensional frailty measurement tool: Frailty Staging System (FSS) [ 20 , 22 ], which evaluated multiple domains of elderly functioning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They used a clinical frailty score in order to assist clinicians in the planning and delivery of perioperative care for frail patients, with subsequent reductions in mortality. In patients with acute hospital admissions due to heart failure, a retrospective cohort study found the incidence of frailty to be 36% and independently associated with mortality at 30 days [ 16 ]. These data are consistent with our findings, however, our cohort captured patients from both medical and surgical specialities, with a preponderance of higher frailty scores in elderly patients admitted under medical specialities.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic importance of one of these overarching AHF comorbidities, frailty in the elderly, was examined by Martin‐Sanchez and colleagues . Frailty has been defined as a “clinically recognizable state of increased vulnerability resulting from aging‐associated decline in reserve and function across multiple physiologic systems such that the ability to cope with an everyday or acute stressor is compromised.” Objectively, the definition put forth by Fried et al.…”
mentioning
confidence: 99%